Linking Shyness With Social and School Adjustment in Early Childhood: The Moderating Role of Inhibitory Control. Issue 5 (4th July 2018) - Sette, Stefania; Hipson, Will E.; Zava, Federica; Baumgartner, Emma; Coplan, Robert J.
ABSTRACT: Research Findings : The aim of the present study was to examine the moderating role of inhibitory control (IC) in the associations between shyness and young children's social and school adjustment. Participants were 112 Italian children ( M  = 56.85 months, SD  = 10.14) enrolled in preschool. Parents and teachers assessed child shyness and IC as well as indices of social and school adjustment. Children were interviewed to assess vocabulary. Results from hierarchical multiple regression analyses revealed several significant interaction effects between shyness and IC in the prediction of outcome variables. Follow-up simple slope analyses indicated that among children with higher levels of IC, shyness was negatively related to prosocial behavior and popularity. In contrast, among children with lower levels of IC, shyness was positively associated with regulated school behaviors. Practice or Policy : The findings provide evidence to suggest that the combination of shyness and IC may contribute to children's behavioral rigidity, which in turn may promote social and school adjustment difficulties.